Assessment of coronary reperfusion in patients with myocardial infarction using fatty acid binding protein concentrations in plasma. Issue 3 (1st March 2001) - de Groot, M J M; Muijtjens, A M M; Simoons, M L; Hermens, W T; Glatz, J F C
Abstract : OBJECTIVE: To examine whether successful coronary reperfusion after thrombolytic treatment in patients with confirmed acute myocardial infarction can be diagnosed from the plasma marker fatty acid binding protein (FABP), for either acute clinical decision making or retrospective purposes. DESIGN: Retrospective substudy of the GUSTO trial. SETTING: 10 hospitals in four European countries. PATIENTS: 115 patients were treated with thrombolytic agents within six hours after the onset of acute myocardial infarction. Patency of the infarct related artery was determined by angiography within 120 minutes of the start of thrombolysis. MAIN OUTCOME MEASURES: First hour rate of increase in plasma FABP concentration after thrombolytic treatment, compared with increase in plasma myoglobin concentration and creatine kinase isoenzyme MB (CK-MB) activity. Infarct size was estimated from the cumulative release of the enzyme α hydroxybutyrate dehydrogenase in plasma during 72 hours, or from the sum of ST segment elevations on admission. Logistic regression analyses were performed to construct predictive models for patency. RESULTS: Complete reperfusion (TIMI 3) occurred in 50 patients, partial reperfusion (TIMI 2) in 36, and no reperfusion (TIMI 0+1) in 29. Receiver operating characteristic (ROC) curve analyses showed that the best performance of FABP was obtained when TIMI scores 2 and 3 were grouped and compared with TIMI score 0+1. The performance of FABP as a reperfusion marker was improved by combining it with α hydroxybutyrate dehydrogenase infarct size, but not with an early surrogate of infarct size (ST segment elevation on admission). In combination with infarct size FABP performed as well as myoglobin (areas under the ROC curve 0.868 and 0.857, respectively) and better than CK-MB (area = 0.796). At optimum cut off levels, positive predictive values were 97% for FABP, 95% for myoglobin, and 89% for CK-MB (without infarct size, 87%, 88%, and 87%, respectively), and negative predictive values were 55%, 52%, and 50%, respectively (without infarct size, 44%, 42%, and 34%). CONCLUSIONS: FABP and myoglobin perform equally well as reperfusion markers, and successful reperfusion can be assessed, with positive predictive values of 87% and 88%, or even 97% and 95% when infarct size is also taken into account. However, identification of non-reperfused patients remains a problem, as negative predictive values will generally remain below 70%.